PERSEPSI MASYARAKAT TERHADAP PELESTARIAN HUTAN MANGROVE DENGAN PENDEKATAN NEP (NEW ENVIRONMENTAL PARADIGM) (Studi Kasus Kelurahan Kota uneng dan Desa Talibura Kabupaten Sikka) - Apelabi, Gabriel Otan (Gema Wiralodra, 2019)
Generally vast of mangrove forest decrease because of deforestations and converted into cultivation area. Mangrove forest damage also caused coastal erosion and seawater intrusion, which makes the people suffer losses. Since 2000, the coastal area in Kota Uneng Village tend to face extra land area which followed by the growth of mangrove forest vegetation. The people of Kota Uneng Village and Talibura Village has also aware of the important role of the mangrove forest in their area, so the activity of mangrove deforestation gradually reduced. Program Mitra Bahari (PMB) is the cooperation program between Maritime and Fisheries Affairs and College in empowering fisheries society. PMB, which found on 2007, encourages people to conserve mangrove ecosystem in Kota Uneng and Talibura. The participation of people in managing mangrove conservation area will make a positive impact on the increasing of environmental conservation, people?s awareness and social economic life, without damaging the environment. Research was held in Kota Uneng Village and Talibura Village, Sikka Regency, East Nusa Tenggara Province. Research method was explorative by using quantity method. Data collected by direct observation and interview. Sample used in the research was the people of Kota Uneng Village and Talibura Village, in The Mount of 60 respondent. Data was analyzed using independent sample T-test and Kruskal Wallis test. The obtained result of independent sample T-test: based on sex, there is no differentiation for balance of nature factor, man over nature factor and limit to growth factor on male and female. Based on marriage status, there is no differentiation for balance of nature factor, man over nature factor and limit to growth factor on marriage status. Based on location, there is the differentiation for the balance of nature factor based on the town and country location. There is no differentiation for man over nature factor and limit to growth factor based on the town and country location. Result of the Kruskal Wallis Test: Based on the education, there is no differentiation for the balance of nature factor and man over nature factor based on the level of education. Based on age, there is no differentiation for the balance of nature factor, man over nature factor, and limit to growth factor based on the age. Based on the income, there is no differentiation for the balance of nature factor, man over nature factor, and limit to growth factor based on the income. Based on the job, there is no differentiation for the balance of nature factor, man over nature factor, and limit to growth factor based on the job.